2020
DOI: 10.2147/cmar.s278354
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Autophagy-related Proteins in Human Gastric Cancer

Abstract: Autophagy-related proteins (ATG) play a crucial role in autophagy. Recently, the functions of autophagy in cancer have been gathering attention. However, the prognostic value of ATGs in gastric cancer (GC) has not been explored. Methods: The Kaplan-Meier plotter (KM plotter) online database was used to examine the value of ATGs gene expression levels in overall survival (OS) prediction in GC patients with different clinical stage, differentiation, gender, HER2 status, and therapeutic strategy. In vitro experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Autophagy influences tumor metastasis, EMT, apoptosis, and drug resistance [ 22 ]. In gastric cancer, the expression pattern of Beclin1, LC3, and P62/SQSTM1, which are autophagy-related genes, predicts the prognosis of the tumor [ 23 25 ]. Another study has also identified 4 genes (GRID2, ATG4D, GABARAPL2, and CXCR4) as a potential prognostic marker for predicting the prognosis of GC patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy influences tumor metastasis, EMT, apoptosis, and drug resistance [ 22 ]. In gastric cancer, the expression pattern of Beclin1, LC3, and P62/SQSTM1, which are autophagy-related genes, predicts the prognosis of the tumor [ 23 25 ]. Another study has also identified 4 genes (GRID2, ATG4D, GABARAPL2, and CXCR4) as a potential prognostic marker for predicting the prognosis of GC patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more targets of VE-822 have been identi ed [33,34]. In this study, screening of CellMiner drug database which include approved drugs in clinical trials revealed that OTUD1 expression was correlated with drug sensitivity of VE-822.…”
Section: Introductionmentioning
confidence: 93%
“…First, it can eliminate the injured cellular constituents or whole cells. Second, the energy or nutrients as a result of degradation can provide malignant cells nutrition or be recycled for apoptosis-associated protein synthesis of apoptosis relative proteins[ 55 ]. Specifically, autophagy participates in oncogenesis and tumor progression via two main pillars: a defective pro-death and an excessive pro-survival action.…”
Section: The Autophagic Component Of Carcinogenesismentioning
confidence: 99%
“…Other investigators, by introducing the Kaplan–Meier plotter online database to assess the value of ATG gene expression levels in overall survival prediction in GC patients with different clinical stage, differentiation, gender, HER2 status and therapeutic strategy showed the following: increased levels of ATG3 , ATG4C , ATG5 and ATG10 mRNA were correlated with prolonged overall survival, whereas high levels ATG4B , ATG7 , ATG12 , ATG16L1 and TECPR1 mRNA were correlated with negative overall survival in patients with GC. Therefore, individual ATG estimation by using Kaplan-Meier plotter analysis may offer a guide to clinical therapeutic strategy by means of individualizing gene therapy for GC patients[ 55 ].…”
Section: The Autophagic Component Of Carcinogenesismentioning
confidence: 99%